British Virgin Islands : Financial Sector Assessment Program Update Documentation; Technical Note on Mutual Fund Regulation. (IMF Staff Country Reports; Country Report ;, 2010)
In a previous assessment, it was concluded that the British Virgin Islands (BVI) regulatory system governing securities markets functioned well overall, but required improvement in certain areas. Those areas are implemented with regulatory code, Securities and Investment Business Act (SIBA), related regulations, and the public funds code. The standards and eligibility of those who wish to manage or administer a mutual fund are determined by the Financial Services Commission (FSC) under the authority granted by statute. A mutual fund can be organized as a corporation, unit trust, or partnership.